The Strait of Malacca and Strait of Hormuz: A Brief Historical Review (KEMANUSIAAN The Asian Journal of Humanities, 2023)
This study attempts to revisit two prominent trading networks between the Arab world and the Malay archipelago, namely the Strait of Malacca and the Strait of Hormuz, which historically linked the two worlds. This historical linkage is made possible via visitations by the Arab-Persian traders to the Malay world and the Malay traders’ visits to their destinations. Given the geopolitical environments they have experienced in the past and present, there is no denying the immense significance of these straits to Malaysia and the Kingdom of Oman, respectively. They had contributed abundantly in the past to Malaysia and the Kingdom of Oman, as well as to the countries bordering the two straits. Nonetheless, the study argues that given the current unstable world conditions, the safe navigation of both straits is increasingly vulnerable. It also highlights some socioeconomic and political dynamism, which reveal historical changes and continuities that have occurred in the past and present. The situation here seems critical since both straits have established themselves as major world shipping lanes from the west to the east and vice versa. In short, the study investigates the current issues and how small countries like Malaysia and the Kingdom of Oman handle conflict in the most strategic and effective way.